2010
DOI: 10.1111/j.1540-8175.2010.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Real Time “Live 3D” Echocardiography to Visualize the Stenotic Aortic Valve

Abstract: A simplified 3D technique that is a "thick slice" 2D examination, can obtain AS AVA more often than a "thin slice" 2D echocardiogram. This 3D AVA correlates well with 2D AVA but is smaller and correlates better with CE AVA suggesting that the effective AS orifice is not planar but is more of a "tunnel" than a "flat ring."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Quantification of Aortic Valve Area Three-dimensional echocardiography has been used to improve aortic valve area quantification with either planimetry [100][101][102][103] or the continuity equation. 104,105 Three-dimensional TTE planimetered aortic valve area has been reported to be feasible in 92% of patients, with measured values correlating well with 2D TEE planimetry and transthoracic echocardiography-derived continuity values.…”
Section: Clinical Validation and Applicationmentioning
confidence: 99%
“…Quantification of Aortic Valve Area Three-dimensional echocardiography has been used to improve aortic valve area quantification with either planimetry [100][101][102][103] or the continuity equation. 104,105 Three-dimensional TTE planimetered aortic valve area has been reported to be feasible in 92% of patients, with measured values correlating well with 2D TEE planimetry and transthoracic echocardiography-derived continuity values.…”
Section: Clinical Validation and Applicationmentioning
confidence: 99%
“…In a big population of patients with aortic stenosis representing actual clinical practice, evaluation of anatomical valvular area with 3DTEE in patients with AVS was possible in 92% of cases. Although it represents a good feasibility rate, the result is slightly worse than previous reports of selected populations . The investigators that performed the 3DTEE were experienced and the studies of their learning period were not included in the sample, which represents an aged population.…”
Section: Discussionmentioning
confidence: 89%
“…The planimetry of aortic valve area (AVA) with 3D echocardiography provides an anatomic measure of valvular orifice at the proper position of cusp tips, overcoming the problems of valvular orifice slanting and systolic valve annular motion . Real time three‐dimensional transesophageal echocardiography (3DTEE) has been shown to be feasible and reliable in the evaluation of aortic valve stenosis grade as compared with conventional transthoracic echocardiography (TTE) in small sets of patients, yet some disagreement grade was found . 3DTEE is not affected by poor transthoracic acoustic windows, but is sensitive to several factors as shadowing caused by valvular calcification, unrest of uncomfortable patients, and high or irregular heart rates as frame rate is characteristically lower than in 2D cross‐sectional imaging.…”
mentioning
confidence: 99%
“…The most studied application of 3D echocardiography has been direct 3D‐guided 2D planimetry of the aortic valve area . The studies showed high feasibility (92%–100%) and reproducibility of this approach (Table ) . Reference and comparator methods included continuity equation based on 2DTTE, 2DTEE and TTE planimetry, computed tomography, and invasive measurements.…”
Section: Aortic Stenosismentioning
confidence: 99%